"Mandem vir seus parentes": a Sociedade Promotora de Imigração em São Paulo (1886-1896) - Petri, Kátia Cristina (2010)
I propose a reflection on the question of work in coffee plantations in São Paulo and how the discussions, which have sought alternantives for the rural labor with the end of slavery, were conducted. We can not say that immigration was a consensus among the farmers, by contrast, throughout the period that it was present, immigration was the target of criticism from different parts of society. The time clipping has, in Immigration Promoted Society, a mounting of the whole apparatus around the arrival of immigrants, through the correspondence sent by their relatives and friends. is in chronological Society Promoting Immigration This aspect is what makes difference between the immigrant project from the other ones which were set previously, or even in the period of its operation, that is, even being the link of the significant immigrant influx, Promoter is going to take as prerogative an indication to immigrate. Only listed families, that were under the auspices of the project, therefore, is a grant program for immigration, only through it is that the subsidy was paid, both for those who immigrated under his responsibility, as the spontaneous who requesting reimbursement or even those who traveled with the encouragement of the general government